Kolonialisme dan kristianisasi Melayu di Sarawak 1850-1950 - Nordi Achie (Penerbit Universiti Malaysia Sabah, 2013)
History of colonial administrators and religous aspect on colonization peroid in Sarawak, Malaysia.